Banking Deregulation and Industry Structure: Evidence from the French Banking Reforms of 1985 - BERTRAND, MARIANNE; SCHOAR, ANTOINETTE; THESMAR, DAVID (Journal of Finance, 2007)
ABSTRACT We investigate how the deregulation of the French banking industry in the 1980s affected the real behavior of firms and the structure and dynamics of product markets. Following deregulation, banks are less willing to bail out poorly performing firms and firms in the more bank‐dependent sectors are more likely to undertake restructuring activities. At the industry level, we observe an increase in asset and job reallocation, an improvement in allocative efficiency across firms, and a decline in concentration. Overall, these findings support the view that a more efficient banking sector helps foster a Schumpeterian process of “creative destruction.”